Contribution in the Review of the Literature on Productivity in the Scope of Business Economics - Ferreira, Leonor Fernandes; Torres, Miguel Matos (Review of Business Management, 2007)
This paper discusses the concept of productivity of the firm and its evolution, as well as the techniques that may be used to manage and measure it. The three-fold structure adopted in the literature review relates to the chronological order of publication and is based upon common characteristics identified in past research. Section 2 includes studies on productivity published until the eighties of the last century and concerns to normative-deductive research. Section 3 discusses some studies dating from the following two decades and refers to how to manage and measure the productivity of the firm. Section 4 reviews positive (empirical) productivity research, which relates to recent published papers. These studies are usually authored by researchers’ teams from various centers or countries and analyze large amounts of data, making use of databases, computers and statistics, thus, giving some insight on de factum productivity of the firm. The contribution of this research is summarized in Section 5. We conclude that there has been a shift in the research focus: external, normative and descriptive studies substitute internal, managerial and positive research on the productivity of the firm. Key-words: Productivity. Factor of production. Efficiency. Firm. Literature review.